Design of "One-key" security measures system for smart substation. (September 2020) - Jin, Xinming; Ren, Jiangbo; Bu, Mingxin; Tan, Chang; Chen, Haibin; Geng, Shaobo; Mao, Jianzhong
Abstract: With the continuous advancement of technology and the ever-increasing demand for information digitization in power systems, smart substations have become the most mainstream substations currently used in China. The secondary circuit and pressure plate of the intelligent substation are virtual forms constructed by internal software. There is no obvious electrical disconnection point, so there is a big difference in operation and maintenance and repair methods from conventional substations. Combined with the requirements of the intelligent station maintenance business, this paper proposes to deploy a "one-click" security system in the station control layer monitoring system of the intelligent substation. This system is only used as an additional module and does not depend on the software and hardware structure of the station control layer. It is of great significance to effectively improve the efficiency of intelligent secondary equipment operation inspection and better guarantee the safe and stable operation of the power grid.